2022
DOI: 10.7554/elife.74342
|View full text |Cite
|
Sign up to set email alerts
|

Endoplasmic reticulum stress activates human IRE1α through reversible assembly of inactive dimers into small oligomers

Abstract: Protein folding homeostasis in the endoplasmic reticulum (ER) is regulated by a signaling network, termed the unfolded protein response (UPR). Inositol-requiring enzyme 1 (IRE1) is an ER membrane-resident kinase/RNase that mediates signal transmission in the most evolutionarily conserved branch of the UPR. Dimerization and/or higher-order oligomerization of IRE1 are thought to be important for its activation mechanism, yet the actual oligomeric states of inactive, active, and attenuated mammalian IRE1 complexe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
25
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(43 citation statements)
references
References 69 publications
5
25
0
Order By: Relevance
“…We anticipate that these long-lived interactions are crucial for providing sufficient time for transmitting the information through the membrane bilayer to initiate the autophosphorylation of the kinase domains leading to activation of its RNase domain. This model is in line with the recent data, which showed a lag between IRE1α oligomerization and its trans-autophosphorylation activity in cells 31 . In our experiments, we used a simple membrane composition, and thus future studies are necessary to assess how changes in the membrane composition during ER stress might regulate IRE1α clustering 25,26,43 .…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…We anticipate that these long-lived interactions are crucial for providing sufficient time for transmitting the information through the membrane bilayer to initiate the autophosphorylation of the kinase domains leading to activation of its RNase domain. This model is in line with the recent data, which showed a lag between IRE1α oligomerization and its trans-autophosphorylation activity in cells 31 . In our experiments, we used a simple membrane composition, and thus future studies are necessary to assess how changes in the membrane composition during ER stress might regulate IRE1α clustering 25,26,43 .…”
Section: Discussionsupporting
confidence: 93%
“…Semi-quantitative polymerase chain reaction (PCR) and quantitative real-time PCR (qRT-PCR) analyses revealed that IRE1α LNYL-mNG mutant exhibited impaired XBP1 mRNA splicing activity compared to wild type IRE1α-mNG, indicating that the interfaces formed by the LNYL region in IRE1α LD play an important role in forming active IRE1α assemblies in cells (Fig 5B,C). Instead, IRE1α TLPL-mNG splicing activity was only slightly diminished 31,42 (Fig 5B,C). These data suggested that the mutation in the interface formed by TLPL segment can be compensated by formation of other protein interfaces in cells.…”
Section: The Disordered Regions In Ire1α Ld Are Important For Its Clu...mentioning
confidence: 92%
See 2 more Smart Citations
“…Many of the experiments that observe IRE1 clustering overexpressed IRE1. Despite work indicating that IRE1 clusters are important for UPR signaling, 13,14,20,38 recent work 50,51 indicates that endogenous IRE1 levels in certain mammalian cells (approximately 1 mm À2 ) are significantly lower than when IRE1 is overexpressed, and that large IRE1 clusters may not be required for UPR signaling. However, it is noted that IRE1 concentration can vary between cells and for cells in pathological states.…”
Section: Discussionmentioning
confidence: 99%